Pengaruh Beberapa Jenis Bahan Aktif Herbisida Dan Waktu Pemasangan Perangkap Terhadap Populasi Serangga Elaeidobius kamerunicus (Coleoptera: Curculionidae) Di PPKS Marihat Kebun Kalianta - Ardi Ansyah; Maryani Cyccu Tobing; Suzanna Fitriany Sitepu; Agus Eko Prasetyo (Universitas Sumatera Utara, 2018)
The objective of this research was to study the influence of herbicides and time of trapping after application on population of weevil Elaeidobius kamerunicus. This research was conducted at Oil Palm Plantation Kalianta, Riau and at Laboratory of Indonesian Oil Palm Research Institute (IOPRI), using method of Factorial Randomized Group Design with 2 factors, the first was herbicides (without herbicide, methyl metsulfuron 100 gr/ha, paracuat 400 cc/ha, glyfosat 400 cc/ha) and the second factor is time of traps (2 hours after applications, 48 hours after application and 72 hours after application) with three replications.The results at field showed that population of weevil E. kamerunicushigher in treatment without herbicide compared to treatment using herbicide at male flower was 334 adults/spicelet and female flower was 689 adults/bunch. Treatment 72 hours after applications traping at male flower on population of weevil E. kamerunicus was 282 adults/spicelet. Keywords: Elaeidobius kamerunicus, Herbicide, oil palm, population.